STUDI KOMPARASI EKSPERIMENTAL BALOK BETON BERTULANG DENGAN MENGGUNAKAN ABAQUS CAE SEBAGAI PERBANDINGAN NILAI BEBAN DAN LENDUTAN - Bernando, Nofri; Jauhari, Zev Al; Garcya, Muhammad Gala (Jurnal TeKLA, 2024)
Effective field testing of concrete structures requires a great deal of rigor and understanding the response and behavior to concrete loads. The bending of the beam tends to be smaller, so reinforcing steel is used to increase the displacement of the beam. However, errors often occur in the implementation so that there is often a decrease in the quality of the concrete. The arrangement of the reinforcement is not in accordance with the requirements for the load received, so it is necessary to create a model according to the load to be applied without conducting multiple trials (trial errors). The abaqus CAE software is a modeling application that belongs to the Finite Element. Modeling reinforced concrete beams in the abaqus application for this study is expected to get results close to experimental tests in the field. namely the comparison between experimental test results of reinforced concrete beams with the results of analysis in the abaqus CAE software. The results of flexure testing of reinforced concrete beams in the field obtained a maximum load value of 106.22 KN with a deflection of 1.126 mm. While the modeling of reinforced concrete beams in the abaqus application obtained a maximum load value of 146.203 KN with a deflection of 4.83 mm.